Reactivity of allyl methyl sulphide, the in-vitro metabolite of garlic, with some amino acids and with phospholipid involved in viral infections. Issue 1 (2nd January 2022) - Sinha, Anil K.; Farooqui, Saleem A.; Sharma, Ankita; Mishra, Ankit; Verma, Vikas
Abstract: Garlic, as well as several natural food ingredients such as basil, ginger, turmeric, cinnamon, clove, pepper etc., has long been traditionally used as routine anti-viral and anti-bacterial remedy. Allyl methyl sulfide (AMS) is reportedly a persistent main active metabolite component of allicin after garlic ingestion accounting for at least 90% of the allicin consumed. Several studies have reported the presence of AMS in organs such as lung, kidney etc. and body fluids such as mucous, and blood-plasma. Glycoproteins of enveloped viruses are actively involved in viral pathogenesis. N-acetylneuraminic acid (sialic acid) and N-Acetylglucosamine, are some of the vital amino acids involved in several viral infections using glycoproteins via glycosylation. Simulations studies based on First-principles density functional theory show that these amino acids attach with AMS, and the reactions are thermodynamically spontaneous (ΔG and ΔS negative are at 310.15 K as well as lower and higher temperatures). Further, phospholipid phosphatidylethanolamine (a component of some viral envelops) also attaches readily with AMS and the reaction is spontaneous. AMS molecules attachment with viral phospholipids and amino-acids involved in viral infection would denature the virus and prevent its attachment to the host cell. Communicated by Ramaswamy H. Sarma